การบริหารงานพัสดุของโรงเรียนในสังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาเลย เขต 3 - ปิ่นคำ, ว่าที่ร้อยตรีเจริญชัย (วารสารศรีล้านช้างปริทรรศน์, 2016)
บทความวิจัยนี้มีวัตถุประสงค์ 1) เพื่อศึกษาการบริหารงานพัสดุของโรงเรียนในสังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาเลย เขต 3 2) เพื่อเปรียบเทียบการบริหารงานพัสดุของโรงเรียนในสังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาเลย เขต 3 จำแนกตามเพศ อายุ ระดับการศึกษา ประสบการณ์ในการทำงานและตำแหน่งหน้าที่ ในการวิจัยครั้งนี้กลุ่มตัวอย่างได้แก่ ผู้บริหารโรงเรียนและครูผู้ปฏิบัติงานเจ้าหน้าที่พัสดุของโรงเรียนในสังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาเลย เขต 3 มีจำนวน 222 คน กลุ่มตัวอย่าง 144 คน จากรูปแบบตารางเครซี่และมอร์แกน (Krejcie Morgan) เครื่องมือที่ใช้ในการวิจัยคือแบบสอบถาม สถิติที่ใช้ในการวิเคราะห์ข้อมูลมี 2 ประเภท ได้แก่ สถิติเชิงพรรณนา คือค่าความถี่ ค่าร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน และสถิติเชิงอนุมาน คือ การทดสอบค่าที่ (t-test) และการทดสอบความแปรปรวนแบบทางเดียว (F-test or One-Way ANOVA) และถ้าพบความแตกต่างของค่าเฉลี่ยเป็นรายคู่ด้วยวิธีการของเชฟเฟ่ (Scheffé) ผลวิจัยพบว่า ผู้บริหารโรงเรียนและครูผู้ปฏิบัติงานเจ้าหน้าที่พัสดุ มีระดับการปฏิบัติงานการบริหารงานพัสดุ โดยรวมอยู่ในระดับมาก เมื่อพิจารณาเป็นรายด้าน พบว่าด้านการควบคุมพัสดุมีระดับการปฏิบัติงานสูงสุด เมื่อเปรียบเทียบระดับการปฏิบัติงานของผู้บริหารโรงเรียนและครูผู้ที่ปฏิบัติงานหน้าที่พัสดุสังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาเลย เขต 3 พบว่า มีความแตกต่างกันเฉพาะระดับการศึกษา โดยระดับการศึกษาต่ำกว่าปริญญาตรี สูงกว่า ระดับปริญญาตรี และสูงกว่าระดับปริญญาตรีตามลำดับ           A substance composes this have 1) objective for studies work inventories administration of affiliated with office area education elementary education school, 3 2) borders for compare with work inventories administration s of affiliated with office area education elementary education school, 3 borders separate to follow the gender, age, education level , the experience in the work and positions. the sample for example, school executive and executor officer inventories teacher of affiliated with office area education elementary education school, 3 borders have 222 persons amount, 144 persons samples, from table format K and small axle hill, (Krejcie Morgan), a tool that use in the research is the questionnaire, the statistics that use in data analysis has 2 a kind , for example, manner statistics describes, be frequency value , percentage value, average, the part deviates the standard , and manner statistics estimates, be, value test at, (t-test), and the vary test like [ model ], The one way , (F-test or One-Way ANOVA), and if, meet the difference of the average is lay a pair with the way of, (Scheff).The results of the research were as follows: School executive and executor officer inventories teacher, be high class work practice administrates the inventories, generally stay in many levels, when , consider lay a side, meet that, supervision inventories side is high class. Work topmost practices when, compare with practice work level of school executive and a teacher who perform one's duty the inventories are under area education elementary education office, 3 borders meet that, there is the difference especial education level, by the level is uneducated more the bachelor's degree, tall more , bachelor's degree level , and tall more bachelor's degree level respectively.